Rapid phosphatidic acid accumulation in response to low temperature stress in Arabidopsis is generated through diacylglycerol kinase - Arisz, Steven A.; van Wijk, Ringo v.; Roels, Wendy; Zhu, Jian-Kang; Haring, Michel A.; Munnik, Teun (Frontiers in Plant Science, 2013)
Phosphatidic acid (PtdOH) is emerging as an important signaling lipid in abiotic stress responses in plants. The effect of cold stress was monitored using 32P-labeled seedlings and leaf discs of Arabidopsis thaliana. Low, non-freezing temperatures were found to trigger a very rapid 32P-PtdOH increase, peaking within 2 and 5 min, respectively. In principle, PtdOH can be generated through three different pathways, i.e., (1) via de novo phospholipid biosynthesis (through acylation of lyso-PtdOH), (2) via phospholipase D hydrolysis of structural phospholipids, or (3) via phosphorylation of diacylglycerol (DAG) by DAG kinase (DGK). Using a differential 32P-labeling protocol and a PLD-transphosphatidylation assay, evidence is provided that the rapid 32P-PtdOH response was primarily generated through DGK. A simultaneous decrease in the levels of 32P-PtdInsP, correlating in time, temperature dependency, and magnitude with the increase in 32P-PtdOH, suggested that a PtdInsP-hydrolyzing PLC generated the DAG in this reaction. Testing T-DNA insertion lines available for the seven DGK genes, revealed no clear changes in 32P-PtdOH responses, suggesting functional redundancy. Similarly, known cold-stress mutants were analyzed to investigate whether the PtdOH response acted downstream of the respective gene products. The hos1, los1, and fry1 mutants were found to exhibit normal PtdOH responses. Slight changes were found for ice1, snow1, and the overexpression line Super-ICE1, however, this was not cold-specific and likely due to pleiotropic effects. A tentative model illustrating direct cold effects on phospholipid metabolism is presented.